Becoming Aware of Inner Self-Critique and Kinder Toward Self: A Qualitative Study of Experiences of Outcome After a Brief Self-Compassion Intervention for University Level Students - Binder, Per-Einar; Dundas, Ingrid; Stige, Signe Hjelen; Hjeltnes, Aslak; Woodfin, Vivian; Moltu, Christian (Frontiers in Psychology, 2019)
This qualitative study investigated ways in which student participants in a three-session self-compassion course became more compassionate toward themselves and challenges related to this change. Ninety-four participants completed an online survey and 12 participants were interviewed face-to-face. First, a thematic analysis of the responses from the online survey was conducted, and then sorted by frequency, indicating their representativeness in the written responses. The following themes were identified: (1) being more supportive and friendlier toward self, (2) being more aware of being too hard on oneself, (3) feeling less alone when having painful feelings, (4) having more acceptance of painful feelings, and (5) feeling more stable and peaceful. These five most frequent themes served as a basis for a structured phenomenological analysis in the next analytic stage. They were used as a template for a content analysis of the interview material. Subsequently, a phenomenological analysis was conducted on the interview transcripts covering the five thematic areas.